Estudo acerca das relações de gênero e suas repercussões sobre o trabalho docente na Rede municipal de ensino de São Paulo - Deodato, Mariana Fonte Boa [UNIFESP] (2020)
The theme of this research is part of the debate on teaching working conditions, with a focus on gender issues, in order to understand the repercussions of gender relations on the work of teachers of the final years of elementary school in the municipal public system of São Paulo. Analyzing the history of women in education, it is possible to verify that their access to schooling was belatedly allowed and the education for them was different comparing to what was offered to men. It can be seen that the feminization of teaching occurred at the same time that teaching work became more precarious and devalued. It is understood that, in a patriarchal society, women's work is considered with lower value and prestige. Thus, the school as a replicator of social inequalities is an environment where sexist practices are reproduced and, often, normalized. Based on the above consideration, the concept of historical materialism is adopted as an investigative approach and the following research question is presented: do gender issues existing inside and outside school affect the relationships in the school environment and teacher’s work, and can they even promote differences in the nature and division of duties between male and female teachers? A quantitative research will purview the following objective: i) to verify whether sex interferes in schooling and teaching functions; besides, from a qualitative perspective, the research aims to investigate: ii) whether gender relations outside school cause effects on teaching work, iii) whether gender inequalities imply an overload of tasks for female teachers, iv) whether precarious working conditions affect more female than male teachers and v) the representations of female teachers about gender roles and stereotypes in their work. For that purpose, it was carried out a quantitative research about the public school servants through the analysis of data provided by the São Paulo Municipal Department of Education, and a field research, with semi-structured interviews with teachers, coordinators and principal of two elementary schools of the municipal school system of São Paulo. The main authors supporting the analyzes as a theoretical framework are Joan Scott, Heleieth Saffioti and José Contreras, in addition to contributions from other researchers, such as Dalila Oliveira and Michael Apple. From the analysis made, it can be seen that teachers are subjected to precarious working conditions, such as loss of autonomy, overload of tasks and low salaries. It was also noticed that gender relations mark the teaching work in schools, with women and girls being more exposed to situations of harassment and discrimination. It can also be observed that most women have a lato sensu postgraduation grade due to the fact that this training is, most of the time, distance learning, allowing flexibility of time dedicated to study. It can be noted that women, especially when they are black, face more difficulties to study and, mainly, to participate in training outside the São Paulo municipal education network, due to the accumulation of working hours and domestic tasks. As a result, women are less likely to grown in their careers, to increase their salaries and to access management positions. Nonetheless, racism is also prominent in the school's daily life. Therefore, gender and race issues must be debated both during teacher training and in basic education classes.